IMPACT OF THE COVID-19 PANDEMIC ON BRUXISM AND THE DAILY LIFE OF CHILDREN AGED 7-10 - Marianna Dimitrova; Nadezhda Mitova (Peytchinski Publishing, 2024)
Introduction: In 2020, the global pandemic of COVID-19 significantly affected our daily lives. The youngest students were most affected due to the establishment of distance education, which is associated with social isolation and increased screen time. Aim:To investigate the prevalence and specific risk factors for sleep bruxism associated with the COVID-19 pandemic in children aged 7-10 years, their eating habits and physical activity. Materials and methods: The object of the study are 267 children aged 7-10 years. The examined children underwent a clinical examination, during which the following were registered: dental status and attrition, oral hygiene and orthodontic status. Anamnestic data on nocturnal bruxism, physical activity, dietary habits, and screen exposure were obtained from 241 parents via a questionnaire. The results were statistically processed with SPSS-19. Results: The frequency of bruxism in children aged 7-10 is 21.4% (p<0.05). No increase in its frequency or intensity was found during the pandemic in the studied groups. The average increase in screen exposure during the pandemic was more than 60 minutes per day (p<0.05). In 1/4 of the children, physical activity during the pandemic decreased (p<0.05). In 21.6% of the examined children, the intake of simple carbohydrates increased (p<0.05). Conclusions: Bruxism is a common condition in school-aged children. The restrictive measures during the COVID-19 pandemic have led to a rise in some risk factors for bruxism oral and general health of children aged 7-10 years by increasing their screen exposure, consumption of simple carbohydrates and decreasing their physical activity.